Persephone at Mid-Life: Revisiting Feminist Archetypal Theory in a Personal Journey Through Menopause - Pickard, Susan (Feminist theology, 2024)
This article suggests that feminist archetypal theory provides a helpful and empowering framework through which to understand embodied change as experienced in contemporary times. A mainstream approach associated with second-wave feminism, it has fallen victim to poststructuralist critiques and is rarely used, despite a renewed popularity of goddess archetypes in broader lay culture. I argue that this framework deserves revisiting as, in generating positive images and plots, it can serve as a source of empowerment and strength for women and especially so where hegemonic contemporary discourses are overwhelmingly negative and medicalised, as in the case of menopause. Using auto-ethnographic methods, I illustrate this with reference to my own lived experience of menopausal transition. Finally, and just as importantly, I show how this approach configures a different and more holistic kind of knowledge that recognises connection, relationality and communion of self, others and world, rather than separation and domination.